Preparation, characterization and application of a protein hydrogel with rapid self‐healing and unique autofluoresent multi‐functionalities. Issue 1 (8th November 2018) - Chen, Jun; Dong, Qiuchen; Huang, Yikun; Ma, Xiaoyu; Fan, Tai‐Hsi; Bian, Zichao; O'Reilly Beringhs, André; Lu, Xiuling; Lei, Yu
Abstract: A smart hydrogel with dual self‐healing and autofluoresent functionalities is presented. The protein hydrogel is fabricated by denaturing bovine serum albumin in a basic environment. Upon gelation, autofluorescence is induced and the protein hydrogel can be excited by a wide range of spectrum, ranging from 320 to 520 nm. It was also found that the as‐prepared autofluorescent protein hydrogel possessed rapid and repetitive self‐healing capability. Without any external stimulus, more than 90% recovery of the mechanical strength can be obtained within 10 min after destruction. Moreover, the as‐prepared hydrogel exhibits excellent biocompatibility and cell attachment property after its pH adjustment to neutral pH, while both autofluorescence and self‐healing properties were still retained. This study suggests a promising means to prepare multi‐functional protein hydrogel with dual physicochemical functionalities, which holds great potential in biomedical related applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 81–91, 2019.